034 Differences in injury characteristics between athletics disciplines during international athletics championships. (3rd March 2020) - Edouard, Pascal; Navarro, Laurent; Branco, Pedro; Gremeaux, Vincent; Timpka, Toomas; Junge, Astrid
Abstract : Background: Competing in international athletics championships bears the risk of injury. Athletics is composed of different disciplines with different physical, mechanical, technical and psychological demands, leading to different injury rates according to disciplines. However, the specific injury characteristics according to disciplines have not been yet described for high-level athletes during international championships. Objective: To analyse differences in injury characteristics between athletics disciplines during international athletics championships. Design: Prospective study. Setting: 14 international championships from 2007 to 2018. Participants: 8925 male and 7614 female registered international-level athletes. Main outcome measurements: The national medical teams and the local organizing committee physicians reported all newly incurred injuries daily on a standardised injury report form, including the characteristics of each injury: location, type, cause and severity. We analysed differences in injury characteristics distribution between the nine disciplines separately for male and female athletes using Chi 2 -tests, or Fisher' exact test where appropriate. Results: A total of 928 injuries were reported in male and 597 in female athletes. Injury characteristics significantly varied between disciplines for location, type, cause and severity, in both male and female athletes. Thigh muscle injuries were the main injury diagnoses in sprints, hurdles, jumps, combined events and race walking, lower leg muscle injuries in marathon, lower leg skin injury in middle and long distances, and trunk muscle and lower leg muscle injuries in throws. Conclusions: Short-distance running disciplines exposed to thigh muscle injuries, while long-distance running disciplines exposed to lower leg muscle injuries, and disciplines involving plyometric (i.e. jumps or combined events) are associated with musculoskeletal injuries of different locations and types. Strategies for medical service provision, including local organisation, medical teams, supplies, and facilities, in the preparation of and at athletics championships should be discipline-specific and prepared for targeting the main injuries in each discipline as they appear in the program.